RETROSPECTIVE ANALYSIS OF RABIES EPIZOOTIC SITUATION IN MOSCOW REGION IN 2010-2016 - A. V. Paroshin; S. V. Voskresensky; A. A. Mukovnin; A. V. Yenshin; A. Ye. Metlin; K. N. Gruzdev (Ветеринария сегодня, 2018)
Rabies is a viral disease of animals and humans that is characterized by signs of polioencephalomyelitis and is in most cases lethal. This is one of the oldest and most dangerous infectious diseases. As estimated by the WHO this disease is in the top five zoonoses that cause major economic losses; it poses a constant threat to animal and human health and is included in the OIE list of notifiable diseases. Rabies in animals (especially wild carnivores) is one of the most important international criteria (WHO, FAO, OIE) for assessing the biological and environmental safety of human habitat. The Moscow Oblast' is a unique region in Russia, which is an urbanized megalopolis where rabies is reported in animals. Occupying a large territory, it borders on seven Subjects of the Russian Federation with the unfavourable epidemic situation with regard to rabies. This paper presents statistical data on the epizootic situation in the Moscow Oblast, Moscow and neighboring regions in 2010-2016. The dynamics of the epizootic process over the years and the need for its continuous monitoring are shown. In the territory of the Moscow Oblast and neighbouring regions, oral vaccination is one of the main ways to control rabies in animals in the wild. In order to prevent introduction, as well as to ensure prevention and eradication of this transboundary disease, a deeper scientific rationale is required for carrying out a complex of veterinary activities taking into account epizootic processes occurring in the border areas of neighbouring territories.